Nuclear and particle physics - Walet, Niels (The University of Hull)
A third year course in Nuclear and Particle Physics. Could do with a few LHC updates. Contains lecture notes, examples, ... as well as the files used to create these resources. Also has some movies of nuclear collective motion. Discusses: 1 Introduction 2 A history of particle physics 3 Experimental tools 4 Nuclear Masses 5 Nuclear models 6 Some basic concepts of theoretical particle physics 7 The fundamental forces 8 Symmetries and particle physics 9 Symmetries of the theory of strong interactions 10 Relativistic kinematics